Development of Large Platelet Aggregates from Small Aggregates as Determined by Laser-light Scattering: Effects of Aggregant Concentration and Antiplatelet Medication - Tohgi, Hideo; Takahashi, Hiroaki; Watanabe, Katsumi; Kuki, Hiroyuki; Shirasawa, Yoshiaki (Thrombosis and Haemostasis, 1996)
Particle-counting methods that employ light scattering (LS) quantify changes in the number of platelet aggregates of different sizes after the application of an aggregating stimulus. Using the LS method, we studied the effects of aggregant concentration, aspirin administration, and ticlopidine administration on aggregate formation and compared the results with those obtained using the conventional optical density (OD) method. Subjects were 47 controls, 31 patients treated with aspirin (330 mg/day), and 37 patients treated with ticlopidine (200 mg/day). Platelet aggregation after stimulation by 0.5, 1.0 or 5.0 μM ADP, or 0.5, 1.0 or 2.0 μg/ml collagen was determined using both methods. Using the LS method, small (9-25 μm), medium (25-50 μm), and large (50-70 μm) aggregates were counted. In patients untreated with antiplatelet medication, greater concentrations of ADP or collagen generated larger aggregates. Generation of small and medium-sized aggregates showed a significant positive correlation with OD levels after stimulation with 0.5 or 1.0 μM ADP, or 0.5 or 1.0 μg/ml collagen. In patients treated with aspirin, the development of small aggregates into large aggregates was inhibited. Thus, the number of small aggregates increased. Inhibition induced by aspirin was more effective against aggregation after stimulation with collagen than with ADP. In patients treated with ticlopidine, small and medium-sized aggregate formation was inhibited after stimulation with low concentrations of ADP or collagen, but was promoted after stimulation with high aggregant concentrations. The capability of the LS method to quantify different sizes of aggregates after stimulation with low concentration agonists may facilitate investigation of the aggregation process, and of how this process is affected by antiplatelet agents.